PENINGKATAN PEMAHAMAN TERHADAP ILMU KIMIA MELALUI KEGIATAN PRAKTIKUM KIMIA SEDERHANA DI KOTA SOE - Anselmus Boy Baunsele; Maria Benedikta Tukan; Aloisius Masan Kopon; Erly Grisza Boelan; Faderina Komisia; Maria Aloisia Uron Leba; Yustina D. Lawung (Aptekmas Jurnal Pengabdian pada Masyarakat, 2020)
This community service was carried out on two topiks, there are a simple chemical practicum and the socialization of the risk of Plastik waste in Soe City, East Nusa Tenggara Province. This activity aims to increase the people's understanding of the chemical science which is considered dangerous for the organism. The mistake in understanding of chemical concept causes the chemistry science is to difficult to study, even though chemistry has comprehensive  benefits in life, such as in agriculture for fertilizer production, in pharmacy to synthesis the medicine, for culinary to nutrient content estimated, in the livestock sector to make vaccines, in the marine sector to manage the marine product and for environment to overcome the environmental pollution due to the waste. This activity was initiated by the students and lecturers in the Chemical Education Study Program, of Widya Mandira Catholic University with the target being Junior High School students in the Soe city. Simple practicum is done using natural materials around in order to create an easy chemistry lesson. In addition to practicum activities, there are also has a socialization activities about the risk  of Plastik waste, because Plastik waste is an environment problem in the future.